Photocatalytic properties of a new Z-scheme system BaTiO3/In2S3 with a core–shell structure. Issue 20 (11th April 2019) - Wei, Kaili; Wang, Baolai; Hu, Jiamin; Chen, Fuming; Hao, Qing; He, Guannan; Wang, Yinzhen; Li, Wei; Liu, Junming; He, Qinyu
Abstract : It's highly desired to design an effective Z-scheme photocatalyst with excellent charge transfer and separation, a more negative conduction band edge ( E CB ) than O2 /·O2 − (−0.33 eV) and a more positive valence band edge ( E VB ) than ·OH/OH − (+2.27 eV). Abstract : It's highly desired to design and fabricate an effective Z-scheme photo-catalyst with excellent charge transfer and separation, and a more negative conduction band edge ( E CB ) than O2 /·O2 − (−0.33 eV) and a more positive valence band edge ( E VB ) than ·OH/OH − (+2.27 eV) which provides high-energy redox radicals. Herein, we firstly designed and synthesized a core–shell-heterojunction-structured Z-scheme system BaTiO3 @In2 S3 (BT@IS, labelled as BTIS) through a hydrothermal method, where commercial BT was used as the core and In(NO3 )3 · x H2 O together with thioacetamide as the precursor of IS was utilized as the shell material. In this system, the shell IS possesses a E CB of −0.76 eV and visible-light-response E g of 1.92 eV, while the core BT possesses a E VB of 3.38 eV, which is well suited for a Z-scheme. It was found that the as-prepared BTIS possesses a higher photocatalytic degradation ability for methyl orange (MO) than commercial BT and the as-prepared IS fabricated by the same processing parameters as those of BTIS. Holes (h + ) and superoxide radicals (·O2 − ) were found to be the dominant active species for BTIS. In this work, the core–shell structure has inhibited the production of ·OH because the shell IS has shielded the OH − from h + . It is assumed that if the structure of BTIS is a composite, not a core–shell structure, ·OH could be produced during photocatalysis, and therefore a higher photocatalytic efficiency would be obtained. This current work opens a new pathway for designing Z-scheme photocatalysts and offers new insight into the Z-scheme mechanism for applications in the field of photocatalysis.